Christianity and The Indigenous Spiritualties of The Igbo People: From Multi-Religiousness to Synculturation - Nweke, Kizito Chinedu (UIN Sunan Gunung Djati Bandung, 2023)
The Igbo people of Nigeria have historically maintained a rich and dynamic spiritual tradition. The advent of Christianity introduced new dimensions to their spiritual landscape, leading to significant shifts in religious beliefs and practices. This study aims to explore the complexities and transformations in the Igbo spiritual landscape following the encounter with Christianity. It seeks to understand how the Igbo people navigate the coexistence of indigenous spirituality and Christian beliefs, and the resultant socio-cultural and religious dynamics. Employing a literature review and historical analysis, this study systematically examines scholarly works and historical records to unravel the complex interplay between Igbo indigenous spirituality and Christianity. The study found that the Igbo's flexibility in spiritual choices facilitated their rapid conversion to Christianity, influenced by practical advantages such as effective medicine, economic benefits, and efficient foreign social structures. However, this transition also entailed a mental shift, marked by the perception of the Christian God's superiority following military defeats against foreigners. The study highlights the intricate interplay between indigenous spiritualities and Christianity within the Igbo context. It underscores the role of practical factors, cultural adaptation, and perceived spiritual efficacy in shaping religious transformations. These findings contribute to a deeper understanding of religious syncretism and the evolving nature of spiritual beliefs in multi-religious societies.